Extraction optimization, purification, and structural characterization of Yacon polysaccharide: An inhibitor against α-glucosidase/α-amylase - Zhen-Zhou Li; Zhe-Xuan Mu; Shao-Feng Li; Yi-Han Ding; Shadrack Vundi Benjamin; Ruo-Jia Zhu; Xiang-Yu Wang; Zhen-Yu Wang; Hua Zhang (Food Chemistry, 2026)

Sustainable Mn-Ni-Co recovery from complex secondary resources through process-chain engineering and life-cycle environmental assessment - Meichen Pan; Yusheng Tang; Ziyuan Liu; Zhe Tan; Yibo Yang; Panpan Mu; Xiaoguang Zhang (Chemical Engineering Journal, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

The effect of activation on algal char catalyst's physiochemical properties and catalytic performance of algae pyrolysis - Shannan Xu; Zhiqiang Liu; Jiangyi Zhou; Yayuan Xiao; Zhe Zhang; Mao Mu; Shuang Wang (Biomass and Bioenergy, 2026)

Dihydrotestosterone binding to the androgen receptor inhibits apoptosis in ovine undifferentiated granulosa cells via AMH signaling - Yufen Zhao; Haijiang Liu; Zhe Mu; Haijun Li (Animal Reproduction Science, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Evaluation of nitrogen removal performance and metabolic mechanism of a novel salt-tolerant strain Pseudomonas aeruginosa SH3 - Yueyue Zhou; Xiaopeng Wang; Zhe Chen; Ce Shi; Shujian Chen; Lei Liu; Changkao Mu; Chunlin Wang; Weiwei Song (Bioresource Technology, 2025)

Mixing mechanisms of hydrogen-blended natural gas in subsea pipelines: Effects of injection angles - Fenghui Han; Xichen Mu; Ying Wei; Wenhua Li; Zhe Wang (Ocean Engineering, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Research on extraction of valuable metals from solid waste by deep eutectic solvents - A review - Chenye Yang; Jianying Zhao; Panpan Mu; Guosai Jiang; Zhe Tan; Xiaoguang Zhang; Dean Pan (Process Safety and Environmental Protection, 2025)

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

Effects of different lactic acid bacteria on the physicochemical properties, functional characteristics and metabolic characteristics of fermented hawthorn juice - Maozhen Zhao; Yunjuan Mu; Zhiping Shi; Xueqi Wang; Wenhao Liu; Yuhan Zhou; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Chemistry, 2025)

Characterization of SCOBY-fermented kombucha from different regions and its effect on improving blood glucose - Yang Meng; Xueqi Wang; Yunjuan Mu; Maozhen Zhao; Yujia Liu; Huaxi Yi; Lanwei Zhang; Zhe Zhang (Food Bioscience, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Efficient conversion process and mechanism of bromine in bromine-rich saline wastewater - Jixian Wu; Panpan Mu; Xiaoguang Zhang; Guosai Jiang; Zhe Tan; De'an Pan (Journal of Cleaner Production, 2024)

Exploring the biogeography, morphology, and phylogeny of the condylostomatid ciliates (Alveolata, Ciliophora, Heterotrichea), with establishment of four new Condylostoma species and a revision including redescriptions of five species found in China - Yong Chi; Fan Wei; Danxu Tang; Changjun Mu; Honggang Ma; Zhe Wang; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiangrui Chen (Marine Life Science & Technology, 2024)
Species of the ciliate class Heterotrichea Stein, 1859 are a cosmopolitan group of unicellular eukaryotic microorganisms, many of which have been widely used as models in various fields of research such as regenerative biology, functional ecology, environmental toxicology, and symbiotic behavior. However, species identification in the heterotrich family Condylostomatidae, especially the most species-rich and type genus Condylostoma Bory de Saint-Vincent, 1824, remains challenging due to incomplete original descriptions, few reliable distinguishing characters, and overlapping features between different species. This study presents an updated revision of Condylostoma and its related genus Condylostomides da Silva Neto, 1994 based on descriptions of five species, including nine populations collected from China, using both morphological and molecular methods. The main findings are as follows: (1) 43 nominal species and about 130 populations are reviewed, resulting in the recognition of 30 valid species of Condylostoma and eight valid species of Condylostomides ; (2) keys, synonyms, biogeographic distributions and amended/improved diagnoses of all valid species are provided; (3) based on the available data, four new Condylostoma species ( C. marinum sp. nov., C. petzi sp. nov., C. villeneuvei sp. nov., and C. microstomum sp. nov.), one new combination ( Condylostomides minimus (Dragesco, 1954) comb. nov. & nom. corr.), and two corrected names ( Condylostoma ancestrale Villeneuve-Brachon, 1940 nom. corr. and Condylostomides nigrus (Dragesco, 1960) nom. corr.) are suggested; (4) cryptic species are detected and proposed for the first time to form the Condylostoma curvum species complex; (5) three highly confusing Condylostoma species, C. kris , C. spatiosum , and C. minutum , are redefined for the first time based on modern taxonomic methods; (6) a ‘flagship’ species, Condylostomides coeruleus , is recorded for the first time from the continent of Asia, substantially expanding its biogeography; (7) ciliature adjacent to the distal end of the paroral membrane within the family Condylostomatidae is uniformly defined as frontal membranelles and is classified into three patterns according to the arrangement of kinetosomes, which serve as important key features.

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

The Influence of Arctic Sea Ice Concentration Perturbations on Subseasonal Predictions of North Atlantic Oscillation Events - Guokun Dai; Mu Mu; Zhe Han; Chunxiang Li; Zhina Jiang; Mengbin Zhu; Xueying Ma (Advances in Atmospheric Sciences, 2023)

Influence of Arctic Sea-ice Concentration on Extended-range Forecasting of Cold Events in East Asia - Chunxiang Li; Guokun Dai; Mu Mu; Zhe Han; Xueying Ma; Zhina Jiang; Jiayu Zheng; Mengbin Zhu (Advances in Atmospheric Sciences, 2023)

A New Boundary Condition Framework for Particle Method by Using Local Regular-Distributed Background Particles—The Special Case for Poisson Equation - Zhe Sun; Liyuan Dou; Zongbao Mu; Siyuan Tan; Zhi Zong; Kamal Djidjeli; Guiyong Zhang (Journal of Marine Science and Engineering, 2023)
To improve the accuracy of solving the Poisson equation and the efficiency of handling complex boundary shapes in the particle method, this paper proposes a Local Regular-distributed Background Particles (LRBP) as an alternative to traditional boundary handling methods. This method avoids the trouble of arranging virtual particles by introducing background particles, making it suitable for problems with complex boundary shapes. In addition, based on the framework of the weak form Poisson equation, the boundary conditions are easily applied, and the calculations are more accurate. Furthermore, this method allows for different interpolation methods inside and outside the boundary, providing flexibility and versatility. These characteristics are well demonstrated in the validation examples, which indicate its potential to solve complex flow problems.

Vitamin D ameliorates Aeromonas hydrophila-induced iron-dependent oxidative damage of grass carp splenic macrophages by manipulating Nrf2-mediated antioxidant pathway - Hao Sun; Dan Wang; Jingqi Ren; Jiaxi Liu; Zhe Wang; Xinyan Wang; Anying Zhang; Kun Yang; Mu Yang; Hong Zhou (Fish & Shellfish Immunology, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Seismic behaviour of plate-reinforced composite coupling beams with RC slabs - Jianbo Tian; Yong Zhao; Penggang Tian; Wengeng Ren; Zhe Li; Lin Mu; Junlong Lu (Soil Dynamics and Earthquake Engineering, 2023)

Green recovery of Li, Ni, and Mn from spent xLi2MnO3·(1-x)LiMO2 cathode materials: Experimental study and mechanism analysis - Yifan Wang; Qijun Zhang; Xiaoxia Bai; Panpan Mu; Xiaoguang Zhang; Wei Wang; Zhe Tan; Zhenhuan Zhao; De'an Pan (Chemical Engineering Journal, 2023)

Optimal Arctic sea ice concentration perturbation in triggering Ural blocking formation - Guokun Dai; Xueying Ma; Mu Mu; Zhe Han; Chunxiang Li; Zhina Jiang; Mengbin Zhu (Atmospheric Research, 2023)

Efficient removal of trace uranium from nuclear effluents using irradiation-functionalized fibrous adsorbents with very high salt tolerance - Yulong He; Liuhua Mu; Minglei Wang; Lijun Hu; Wanning Ren; Xuanzhi Mao; Xinxin Feng; Mingxing Zhang; Rong Li; Zhe Xing; Jiangtao Hu; Guozhong Wu (Chemical Engineering Journal, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Characteristics of timberline and treeline altitudinal distribution in Mt. Namjagbarwa and their geographical interpretation - Hao-xiang Mu; Fang Han; Bai-ping Zhang; Tian Liang; Zhi-yong Wang; Zhe Wang (Journal of Mountain Science, 2022)

Assessing the effectiveness and function of the water resources tax policy pilot in China - Rulin Ouyang; Enlin Mu; Yibin Yu; Ying Chen; Jiangbo Hu; Haoran Tong; Zhe Cheng (Environment, Development and Sustainability, 2022)

Standard- vs. low-dose rivaroxaban in patients with atrial fibrillation: a systematic review and meta-analysis - Guangyan Mu; Hanxu Zhang; Zhiyan Liu; Qiufen Xie; Shuang Zhou; Zining Wang; Zhe Wang; Kun Hu; Jingyi Hou; Nan Zhao; Qian Xiang; Yimin Cui (European Journal of Clinical Pharmacology, 2022)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

One new cycloartane triterpene glycoside from Beesia calthaefolia - Jin-Yuan Zhao; Li-Hua Mu; Xian-zhe Dong; Yuan Hu; Ping Liu (Natural Product Research, 2016)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

The role of warm North Atlantic SST in the formation of positive height anomalies over the Ural Mountains during January 2008 - Zhe Han; Shuanglin Li; Mu Mu (Advances in Atmospheric Sciences, 2011)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)